The Distributions of Glycogen in the Stomach on Long Tailed Macaque (Macaca fascicularis) during Pre and Postnatal Period - Rahmi, Erdiansyah (Jurnal Kedokteran Hewan, 2008)
The study was done to investigate the glycogen distribution in the stomach of long tailed macaques (Macaca fascicularis). The study used eight individuals of long tailed macaques consist of 6 fetuses (55, 70, 85, 100, 120, and 150 days pregnancy) and 2 infants (10 and 105 days). The gastrict tract were histologically stained using Hematoxyllin-Eosin (HE), and histochemically stained using Periodic Acid Schiff (PAS), to detect glycogen. The results revealed that the histogenesis pattern of stomach glandullar cells are developed in line with the age of the fetuses and infant. We also found that glycogen existance are increase in line with the age in the glandullar stomach. From the present study we concluded that the glycogen distribution in gastrict glandular cells were influenced by the age in the fetal period, while in the infant was under influence of the digestion activities, and the activities of the gastrict glandular cells was already seen at 55 days gestation.